Geographical and Ecological Adaptation of Red Maple (Acer Rubrum) in the Samarkand Region: Lessons from North America - Baratov, K. U.; T. N. , Tuygunov; N. A., Safarova (American Journal of Biodiversity, 2025)
Red Maple (Acer rubrum), a native of eastern North America, is valued for its rapid growth, ornamental autumn foliage, and ecological versatility Recent Uzbek studies highlight its potential for urban and rural greening under local conditions This article reviews Red Maple’s native range, climatic tolerances, and ecosystem services, then examines the prospects and challenges of introducing it to the Samarkand region (including Samarkand city and Okdaryo district) in light of Uzbekistan’s greening initiatives and North American experience.